Scaling procedures issues and applications - Netemeyer, Richard G., 1956- (SAGE, 2003)
'Scaling Procedures' examines the issues involved in developing and validating multi-item self-report scales of latent constructs. It supplies cutting-edge strategies for developing and refining measures.